GLUTARALDEHYDE FIXATION OF ISOLATED EUCARYOTIC NUCLEI : Evidence for Histone-Histone Proximity - Olins, Donald E. (The Rockefeller University Press, 1973)
Isolated chicken erythrocyte nuclei have been incubated with dilute concentrations of the bifunctional cross-linking agent glutaraldehyde (0–20 mM) in order to stabilize histone-histone interactions within the native nucleus. The kinetics of the disappearance of acid-soluble histones, free amino groups, and of individual histones have been observed to be pseudo first-order. Apparent first-order rate constants for the disappearance of individual histones correlate with the lysine mole percent of that fraction and follow the ranking, k (app): F1 > F2C > F2B ≥ F2A2, F2A1, F3. Histone polymers were observed to form very rapidly during the fixation reaction. Partial fractionation and amino acid analyses of these polymers support the view that they are composed principally of cross-linked (F2C)(n) molecules (where n = 2 to ∼8). The rate of glutaraldehyde reaction with free amino groups in histones is drastically reduced in solvents that promote chromatin decondensation (i.e., low ionic strengths in the absence of divalent cations) whereas the formation of cross-linked F2C polymers is less severely reduced. It is proposed that some F2C histones exist in close proximity within the isolated erythrocyte nucleus.